School-Age Children Obesity in Rural Communities with International Migration in Central Mexico. - Carmona González, Maricela (2009)
The objective of the study was to evaluate the prevalence of obesity in school children between 6 and 12 years old. The study was carried out in communities with international migration tradition in the south of the Mexico state. Changes on food habits and life style were also evaluated. The Index of Corporal Mass (ICM) of 276 students was recorded. The 276 students were divided into two groups according to migrant or non-migrant father and by gender to identify differences between groups. Participant observation was used to collecting qualitative data, like eating behaviour. Forty mothers were interviewed to obtain more detailed information about food habits, life style, migration and remittances. The conclusion is that monetary resources from remittances, off-farm activities and governmental programs have an influence on the increasing of obesity and overweight in rural communities.